PENYUSUNAN NORMA TERKAIT KEKERASAN PSIKIS BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2004 MENGENAI PEMBERANTASAN KEKERASAN DALAM RUMAH TANGGA - Endarwati; Sari, Indah (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2024)
Domestic psychological violence cases are based on evidence according to Law Number 23 of 2004 which is the legal umbrella. The formulation of the problem in this research is (1) What was the background to the increased attention to psychological violence in the ratification of Law Number 23 of 2004 concerning the Elimination of Domestic Violence? (2) What are the provisions governing psychological violence in Law Number 23 of 2004 concerning the Elimination of Domestic Violence? This research aims to design legal norms based on a model of evidence that has never existed before so as to create an effective model of evidence for handling cases of domestic psychological violence. This research is based on juridical analysis, the intensity of psychological violence in the household is quite high. Psychological violence has become a public matter as stipulated in Law Number 23 of 2004 as well as national and international legal instruments, unfortunately the existing regulations cannot accommodate the maximum sense of justice because there are substantial weaknesses such as the meaning of psychological violence and the scope is too narrow, criminal sanctions that are too light, as well as the reality of law enforcement officers' less in-depth understanding of psychological violence. There are obstacles in the process of proving psychological violence in terms of presenting witnesses at trial. The model of evidence that has been applied in handling cases of psychological violence in court is not effective. So the author proposes a model of evidence, namely the Private Interrogation Model, where this model of evidence aims to create fair evidence with the principle of respect for household privacy which prioritizes the psychological aspects of the victim. The recommendations in this research are (1) Socializing Law Number 23 of 2004 at all levels, both law enforcement agencies and the community (2) Training for law enforcement officials who deal with psychological violence (3) there is a need for further research related to the model proof of psychological violence so that it can be an option for proof.